2018
DOI: 10.5414/cp203235
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled, phase I study of the safety and pharmacokinetics of namilumab in healthy Japanese and Caucasian men

Abstract: Namilumab was well tolerated in Japanese and Caucasian subjects; namilumab 150 mg had similar pharmacokinetics in both populations, supporting further clinical development of this dose.
.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Namilumab (formerly known as MT203), an IgG1-neutralizing anti-GM-CSF mAb, has been investigated in double-blind, placebo controlled, randomized trials in healthy individuals (NCT02354599) 206 and in RA patients (NCT01317797), 207 which established that namilumab has an acceptable tolerability profile. 206 , 207 Phase 1b (NCT01317797) and phase II studies (NCT02379091) in RA demonstrated efficacy, with the latter study further reporting dose-response effects. 207 , 208 A phase II trial investigating the efficacy of namilumab in plaque psoriasis was also completed (NCT02129777) with no significant difference being recorded for this end point between placebo-treated and namilumab-treated individuals.…”
Section: Clinical Studies With the Blockade Of Gm-csf And Its Receptomentioning
confidence: 99%
“…Namilumab (formerly known as MT203), an IgG1-neutralizing anti-GM-CSF mAb, has been investigated in double-blind, placebo controlled, randomized trials in healthy individuals (NCT02354599) 206 and in RA patients (NCT01317797), 207 which established that namilumab has an acceptable tolerability profile. 206 , 207 Phase 1b (NCT01317797) and phase II studies (NCT02379091) in RA demonstrated efficacy, with the latter study further reporting dose-response effects. 207 , 208 A phase II trial investigating the efficacy of namilumab in plaque psoriasis was also completed (NCT02129777) with no significant difference being recorded for this end point between placebo-treated and namilumab-treated individuals.…”
Section: Clinical Studies With the Blockade Of Gm-csf And Its Receptomentioning
confidence: 99%
“…Namilumab is a fully human IgG1 monoclonal antibody that binds with high affinity to GM-CSF and neutralizes its function ( 225 , 226 ). It has been evaluated in patients with rheumatoid arthritis ( 227 , 228 ), plaque psoriasis ( 229 ) and in hospitalized patients with severe COVID-19 pneumonia ( 230 ).…”
Section: Studies In Pulmonary Sarcoidosismentioning
confidence: 99%